Oficina pedagógica para docentes em formação: concepção de jogos educativos para alunos com dislexia - SILVA, Shirley dos Santos (Universidade Federal do Pará, 2020)
This is a qualitative research of an applied nature, starting from the question-focus: How can the systematization of a pedagogical workshop contribute to the initial formation of teachers, motivating them to elaborate educational games to facilitate the learning of dyslexic students? Thus, this research proposed as general objective to systematize a pedagogical workshop as teaching-learning methodology that approaches theory, practice and creativity, in the initial formation of teachers. For data collection, the procedures of bibliographical research, documentary research were carried out, and the pedagogical projects of the undergraduate courses in History and Pedagogy were analyzed, a questionnaire for primary school teachers and a form for the participants of the Workshop for validation of the product. In this way, the educational product titled "Pedagogical Workshop for Teachers in Training: Designing Educational Games for Students with Dyslexia" was structured and evaluated, with the objective of developing the pedagogical workshop methodology, in order to enable an educational action that articulates theory and practice, providing workshop testing and validation, as well as promoting meaningful learning and the making of educational games for use with dyslexic students. The field of application of the product was the Federal University of Amapá and the Federal University of Pará. The workshop was aimed at academics of undergraduate courses in history, UNIFAP and the UFPA Pedagogy course. The product was submitted to the validation process aiming at its improvement, and for that purpose the panel technique was used. It was important to bring to the academic public the proposal of a workshop, as they demonstrated an interest in the themes of games and dyslexia, as well as understood the meaning of the workshop for teacher training and revealed that they will replicate the practice as a methodological teaching-learning strategy.